ANALISIS USAHA PEMANFAATAN ECENG GONDOK FERMENTASI SEBAGAI PAKAN DOMBA LOKAL JANTAN LEPAS SAPIH - ronald situmorang (Jurnal Peternakan Integratif, 2014)
ABSTRACT Water hyacinth is a weed that can be used to increase profits for farmers. This study aims to analyze the business analysis of utilization fermented water hyacinth onweaning local sheep male. The experiment was conducted at the Laboratory of Animal Biology, Animal Husbandry Study Program, Faculty of Agriculture, University of Sumatera Utara started from August  to November 2013using 20 local weaning sheep with an initial body weight 8.30 ± 1.16 kg. Data taken from 5 treatments consists of P0 : 100 % grass, P1 : 40 % grass + 60 %  fermented  water hyacinth by MOL, P2 : 40 % grass + 60 % fermented  water hyacinth by Trichoderma harzianum, P3 : 100 % fermented  water hyacinth by MOL and P4 : 100 % fermented  water hyacinth by Trichoderma harzianum. This study used  the survey method. The parameters studied were the total production cost, total production, analysis of profit/loss, the revenue cost ratio (R/C ratio) and income over feed cost (IOFC). The results showed the average total cost of production for treatment (Rp) 435.192; 425.116; 453.200; 443.553 and 413.248 respectively. Mean total production for treatment (Rp) 441.400; 440.400; 462.800; 460.300 and 435,000 respectively. Mean analysis of profits / losses for treatment (Rp) 6.208,5; 15.283,9; 9.599,9; 16.747 and 21.752,5 respectively. Mean IOFC for treatment (Rp) 31.806,3; 40.881,7; 35.197,8; 42.344,9 and 48.650,3 respectively. The average R/C ratio for treatment 1,019; 1,037; 1,022; 1,038 and 1,056 respectively. The conclusion of this study is the water hyacinth fermentation utilization  can be increase the profits of local sheep male fattening. Keywords : Business Analysis , fermented water hyacinth , a local male sheep   ABSTRAK Eceng gondok merupakan salah satu gulma yang dapat digunakan untuk meningkatkan keuntungan bagi peternak domba. Penelitian ini bertujuan untuk menganalisis usaha penggunaan eceng gondok fermentasi sebagai pakan domba lokal jantan lepas sapih.Penelitian dilaksanakan di Laboratorium Biologi Ternak Program Studi Peternakan Fakultas Pertanian Universitas Sumatera Utara dari  bulan Agustus sampai bulan Nopember 2013menggunakan 20 ekor domba lokal jantan dengan rataan bobot badan 8,30±1,16 kg/ekor. Data diambil dari 5 perlakuan yaitu P0 : 100% rumput, P1 : 40% rumput + 60% Eceng gondok fermentasi MOL, P2 : 40% rumput + 60% Eceng gondok fermentasi Trichoderma harzianum, P3 : 100% Eceng gondok fermentasi MOL, dan P4 : 100% Eceng gondok fermentasi Trichoderma harzianum. Metode yang digunakana dalah metode survey. Parameter yang diteliti adalah total biaya produksi, total hasil produksi, analisis laba/rugi, revenue cost ratio (R/C ratio) dan income over feed cost (IOFC). Hasil penelitian menunjukkan rataan total biaya produksi (Rp) 435.192; 425.116; 453.200; 443.553 dan 413.248. Rataan total hasil produksi (Rp) 441.400;440.400;462.800;460.300 dan 435.000. Rataan analisis laba/rugi (Rp) 6.208,5; 15.283,9; 9.599,9; 16.747 dan 21.752,5. Rataan IOFC (Rp) 31.806,3; 40.881,7; 35.197,8; 42.344,9 dan 48.650,3. Rataan R/C ratio1,019; 1,037; 1,022; 1,038 dan 1,056. Kesimpulan dari penelitian ini adalah pemanfaatan enceng gondok fermentasi dapat meningkatkan keuntungan penggemukan ternak domba lokal jantan lepas sapih. Kata kunci: Analisis Usaha, eceng gondok fermentasi, domba lokal jantan